Pengaruh Latihan Resistance Band Terhadap Peningkatan Akurasi Shooting Atlet Futsal SMA Negeri 5 Palopo - Fauzan Risky Saputra; Ahmad, Ahmad; Ulpi, Wahyuni (Jurnal Porkes, 2026)
Shooting accuracy is a critical skill in futsal, but observations at SMA Negeri 5 Palopo show that this skill among school athletes is still low, as indicated by the number of missed shots and unstable posture. This study aims to analyze the effect of resistance band training on improving the shooting accuracy of futsal athletes. The method used is a quasi-experiment with a one-group pretest-posttest design. The sample consisted of 15 male athletes selected through purposive sampling. The shooting accuracy test instrument had been tested for validity and reliability (ICC=0.87). The intervention was a 6-week resistance band training program (3 times/week) that focused on leg strength and core stability. The data were analyzed using a Paired Sample T-Test. The results showed a significant increase in the average score from 11.60 (pretest) to 13.67 (posttest) with a mean difference of 2.07 points (p=0.000). The discussion linked this improvement not only to muscle strength adaptation but also to improved motor control, body stability, and movement consistency due to elastic resistance-based functional training. The study concluded that resistance band training effectively improves shooting accuracy and is recommended for integration into school futsal training programs as an economical and multifunctional training tool.